Peran Mekanisme Corporate Governance dalam Meningkatkan Kinerja Keuangan Perbankan di Indonesia - Alifiya Zahra Irmaya Fani; Melati Oktafiyani; Purwantoro; Ratna Herawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effect of the implementation of Good Corporate Governance (GCG) on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2021 to 2023. GCG in this study is proxied through five indicators, namely the board of directors, independent board of commissioners, audit committee, external audit quality, and institutional ownership. Meanwhile, financial performance is measured using Return on Assets (ROA). The number of samples in this study was 87 companies, and the analysis method used was multiple linear regression. The results showed that only the board of directors variable had a significant effect on ROA. This shows that the role of the board of directors is quite important in determining the efficiency and financial performance of the company. Meanwhile, the variables of independent commissioners, audit committees, and institutional ownership do not show a significant influence on the company's financial performance.